2021
DOI: 10.3389/fgene.2021.669928
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of PDZD11 Is Associated With Poor Prognosis and Immune Infiltrates in Hepatocellular Carcinoma

Abstract: Epithelial cells are held together by tight and adherent junctions, which are destroyed by the activation of epithelial-to-mesenchymal transition (EMT). The PLEKHA7-PDZD11 complex has been reported to be important for epithelial cell adhesion and connecting tissues. However, there is no research regarding the expression and role of PDZD11 in liver hepatocellular carcinoma (LIHC) progression. Here, we analyzed PDZD11 mRNA expression and its clinical results in LIHC patient RNA sequencing data based on different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Oncomine, DriverDBV3, GEPIA2, UALCAN, and cBioPortal database analysis and PPI network analysis were performed as previously described [ 5 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Oncomine, DriverDBV3, GEPIA2, UALCAN, and cBioPortal database analysis and PPI network analysis were performed as previously described [ 5 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression of PDZD11 was positively correlated with the infiltration of six immune cells (B cell, CD4+ T cell, CD8+ T cell, macrophage, neutrophil, and dendritic cell) in HCC. In addition, they confirmed that PDZD11 expression was significantly positively correlated with FAM50A expression [ 38 ]. It can be inferred that the expression of FAM50A may also regulate the immune status of HCC patients.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, ferroptosis and cuproptosis have become the focus of much attention in the cancer community due to their unique forms of cell death. They differ from other types of regulated cell death, such as apoptosis, and thus hold great promise for cancer therapy [ 6 , 51 ]. Studies have found that ferroptosis plays a crucial role in HCC treatment through immunotherapy and radiation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%